Respuesta :
Answer:
y = [tex]\frac{1}{27}[/tex]
Step-by-step explanation:
Given
y = [tex]3^{x}[/tex] and (- 3, y) is a point on the graph, then
y = [tex]3^{-3}[/tex] = [tex]\frac{1}{3^{3} }[/tex] = [tex]\frac{1}{27}[/tex]
Answer: The required value of y is [tex]\dfrac{1}{27}.[/tex]
Step-by-step explanation: We are given that the point (-3, y) lies on the graph of the following equation :
[tex]y=3^x~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We are to find the value of y.
Since the point (-3, y) lies on the graph of equation (i), so it will satisfy the equation.
Therefore, substituting (-3, y) in equation (i), we get
[tex]y=3^{-3}\\\\\Rightarrow y=\dfrac{1}{3^3}\\\\\\\Rightarrow y=\dfrac{1}{27}.[/tex]
Thus, the required value of y is [tex]\dfrac{1}{27}.[/tex]